In Vitro Propagation of Elaeocarpus Sphaericus - Chauhan, J. M. S.; Bisht, Prabha; Panwar, Monika; Thakur, Ajay (Indian Forester, 2015)
The present study involves in-vitro clonal propagation of Elaeocarpus sphaericus through axillary bud sprouting and subsequent shoot regeneration. Optimal proliferations of axillary shoot were induced on MS medium supplemented with BAP (1.5 mg/l) and KN (1.5 mg/l). Optimal shoot multiplication was induced on MS medium fortified with BAP (1.5mg/l), KN (1.5 mg/l) and CH (100 mg/l). MS medium supplemented with 1.0 mg/l BAP and 50 mg/l ADS was used for routine sub-culturing of multiple shoots at periodic interval of every 3 weeks. Of the 6 treatments (3 each of IBA and NAA) imposed for rooting of shoots, 1/2 MS + 1.0 mg/l IBA induced 80% rooting. Plants were hardened in vitro and acclimatized in hardening chamber and subsequently transferred to field.